Pelatihan UI/UX Design Sebagai Upaya Pembekalan Soft Skill Bagi Dosen dan Mahasiswa pada PTS Bandar Lampung - Mardiana; Kustiani, Ika; Despa, Dikpride; Sarkowi, Muh. (Nemui Nyimah, 2024)
UI/UX Design is a field of science that is currently trending in Indonesia. The more rapid development of start-up companies, the more job opportunities in the UI/UX field are becoming more numerous and varied. The soft skill ability to design UI/UX for a website or mobile application really needs to be taught and owned by participants at high school and even college levels. Moreover, the need for these skills is in line with the rapid development of Information Technology which means that almost all needs use applications. The problem that PTS Bandar Lampung has, in this case IIB Darmajaya as a partner in this PKM, is the lack of understanding and ability regarding UI/UX design as well as student motivation regarding the UI/UX designer profession. One software that can be used in designing and developing application prototypes is Figma. Figma is a web-based vector graphics editor with additional offline features enabled by desktop applications for macOS and Windows. This PKM aims to enable partners to apply professional principles, procedures and attitudes in designing UI/UX using the Figma application to produce applications that are easy to understand. In this PKM, participants are given UI/UX training and an introduction to Figma as a design tool. The method used in this PKM activity uses the Rapid Application Development (RAD) method. The result of this PKM activity was the partners' understanding of UI/UX and Figma material which was indicated by the pre-test results, which initially averaged only 54.8%, increasing after the training was carried out to an average of 93.6%.